Mortality in a cohort of asbestos-exposed workers undergoing health surveillance - Barbiero, Fabiano (Med Lav, 2018)
BACKGROUND: The coastal area of Friuli Venezia Giulia (FVG) region, north-eastern Italy, was characterized by work activities in which asbestos was used until the early 1990s, particularly in shipbuilding. A public health surveillance program (PHSP) for asbestos-exposed workers was established, although limited evidence exists about the efficacy of such programs in reducing disease occurrence and mortality. OBJECTIVES: To compare mortality in a cohort of 2,488 men occupationally exposed to asbestos, enrolled in a PHSP in FVG between the early 1990s and 2008, with that of the general population of FVG and Italy. METHODS: Standardized Mortality Ratios (SMR), with 95% Confidence Interval (95% CI), for all causes, all cancers, lung (LC) and pleural cancer (PC) were estimated in the cohort and in subgroups of workers with the first hire in shipbuilding that caused asbestos exposure (<1974, 1974-1984, 1985-1994). RESULTS: A strong excess in mortality for PC with reference to FVG (SMR=6.87, 95% CI 4.45-10.17) and Italian population (SMR=13.95, 95% CI 9.02-20.64) was observed. For LC, the FVG-based SMR was 1.49 (95% CI 1.17-1.89) and the Italy-based 1.43 (95% CI 1.12-1.81). Mortality among workers with the first hire in shipbuilding before 1974 was high for PC (FVG-based SMR=8.98, 95% CI 5.56-13.75; Italy-based SMR=18.41, 95% CI 11.40-28.17) and for LC (FVG-based SMR =1.60, 95% CI 1.18-2.11; Italy-based SMR=1.54, 95% CI 1.14-2.03). Further, for LC between 1974 and 1984, the FVG-based SMR was 2.45 (95% CI 1.06-4.82), and the Italy-based SMR was 2.33 (95% CI 1.01-4.60). CONCLUSIONS: This cohort experienced an excess mortality for pleural and lung cancer, compared with regional and national populations. For lung cancer, the excess was stronger in workers with the first hire in shipbuilding before 1985, suggesting a key role of asbestos exposure.